Pengaruh Social Media Marketing, Event Sponsorship, Dan Flash Sale Terhadap Keputusan Pembelian Di Tiktok Shop. (Studi Kasus Mahasiswa FEB Universitas Islam Malang) - Irawan, Ria; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of social media marketing, event sponsorship, and flash sales on purchase decisions in TikTok Shop, focusing on students from the Faculty of Economics and Business at Universitas Islam Malang. The research employs a quantitative approach, utilizing questionnaires distributed to respondents for data collection. The findings indicate a positive and significant impact of all three independent variables on purchase decisions. Social media marketing emerged as the most dominant factor influencing purchase decisions, followed by event sponsorship and flash sales. This research is expected to contribute to marketing practitioners in formulating more effective strategies and to enhance academic understanding of consumer behavior in the digital era. Keywords: Social Media Marketing, Event Sponsorship, Flash Sale, Purchase Decisions, TikTok Shop.